Immobilized cells of Acidithiobacillus ferrooxidans in PVC strands and sultite removal in a pilot-scale bioreactor - Giro, MEA; Garcia, O.; Zaiat, M. (Elsevier B.V., 2006)
The biooxidation of ferrous ion into ferric ion by Acidithiobacillus ferrooxidans can be potentially used for the removal of H2S from industrial gases. In this work, Fe3+ ions were obtained through the oxidation of Fe2+ using the LR strain of At. ferrooxidans immobilized in PVC stands in a pilot-scale bioreactor, while H2S was removed in an absorption tower equipped with Rasching rings. At. ferrooxidans LR strain cells were immobilized by inoculating the bacterium in a Fe2+-mineral medium and percolating it through the support. After complete Fe2+ oxidation, which took around 90 h, the reactor was washed several times with sulfuric acid (pH 1.7) before a new cycle was started. Four additional cycles using fresh Fe2+ mineral medium were then run. During these colonization cycles, the time required for complete iron oxidation decreased, dropping to about 60 h in the last cycle. The batch experiments in the H2S gas removal trials resulted in a gas removal rate of about 98-99% under the operational conditions employed. In the continuous experiments with the bioreactor coupled to the gas absorption column, a gas removal efficiency of almost 100% was reached after 500 min. Precipitate containing mainly sulfur formed during the experimental trial was identified by EDX. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biological oxidation; bioreactors; Acidithiobacillus-ferooxidans; ferrous sulfate; immobilization; hydrogen sulfide